(untitled) (Sinología hispánica. China Studies Review, 2024)
Cognitive linguistics discovers the similarities between cognitive perception and language perception. It provides a solution to the interference caused by the mother tongue when learning a foreign language, Interdisciplinary method will also bring another perspective to L2 students’ language knowledge. This paper tries to analyse the teaching of Metaphor from the cognitive linguistics perspective, reconstructing the Metaphor of language Cognition composition with strategies such as Categories, visualising Image Schemes, building the Cognitive Model, recreating Cognitive Context and teaching Cognitive Grammar. Those strategies do not lie much in linguistics but both visual reasoning and logical thinking. Owing to that, it will bring a different approach to Chinese language teaching.